Intraductal breast masses: Sonographic and mammographic predictors of malignancy - Hesham El Sheikh; Hesham Almohamady Almetaher; Hamdy S. Abdalla; Mohamed M. Shareef (The Egyptian Journal of Radiology and Nuclear Medicine, 2015)
Objective: To determine the ultrasonographic and mammographic features of intraductal breast masses that may be associated with malignancy. Patients and methods: We compared US and mammographic findings with the histopathology in 198 patients with 251 intraductal breast masses. The radiologist assessed US features of the mass, its distance from the nipple, the pattern of duct filling by the mass, whether the mass involved the branch ducts and the presence of abnormal axillary lymph nodes. The mammograms were assessed for the presence of a mass, calcifications, a mass with calcifications and asymmetry. Results: Histopathology revealed 46 malignant masses (18.3%) and 205 benign masses (81.7%). Malignant masses were larger than benign masses, have greater distance from the nipple, commonly filled the duct completely, extended outside the duct, and involved branch duct whereas benign masses commonly filled the duct incompletely and none extended outside the duct or involved branch duct. On mammography, clustered microcalcifications were commonly associated with malignant masses. Conclusion: Intraductal masses completely filled duct, extended outside the duct or involved branch ducts, its distance from the nipple is >15 mm or associated with abnormal axillary lymph nodes on US or microcalcifications on mammography, and all these findings may be associated with malignancy.